2018
DOI: 10.21608/zumj.2018.192421
|View full text |Cite
|
Sign up to set email alerts
|

Between Hope and Risks; Insight on Delayed Sternal Closure Technique Outcomes in Adult Patients underwent Cardiac Operations

Abstract: Background: the delay of sternal closure after cardiac operations may offer the chance for survival in critical conditions; mainly sever hemodynamic instability and uncontrollable bleeding. Many concerns about hope of survival and possible risks especially mediastinitis or wound infection still represent dilemma for surgeons in such situations. The aim of our study is to evaluate the outcomes of delayed sternal closure technique after cardiac operations.Methods:this prospective study included 28 adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In the present study, 3.6% of our patients required DSC procedure, which is similar to recent studies that report an incidence between 3.5-5% [2,5,14], while other studies reported slightly lower incidences ranging between 1-2% [9,12,15] in adult patients. The most common indication for DSC in our center was hemodynamic instability and cardiac edema, followed by arrhythmia and diffuse bleeding, these indications were consistent with previous studies [5,6].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, 3.6% of our patients required DSC procedure, which is similar to recent studies that report an incidence between 3.5-5% [2,5,14], while other studies reported slightly lower incidences ranging between 1-2% [9,12,15] in adult patients. The most common indication for DSC in our center was hemodynamic instability and cardiac edema, followed by arrhythmia and diffuse bleeding, these indications were consistent with previous studies [5,6].…”
Section: Discussionsupporting
confidence: 91%
“…A broad variety of mortality rates were reported, which might be explained by a wide variation of preoperative and intraoperative risk factors, as well as the complexity of the procedures. Yasa et al [12] reported a mortality rate of 27%, Boeken et al [5] also in his large series of 179 patients reported an overall mortality of 29%, other studies reported higher rates of mortality over 30% [9,14,16]. On contrary, few studies with different numbers of patients and a variety of procedures reported less overall Heart Surgery Forum E215 mortality rates of 16% and 10% [11,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations